2017
DOI: 10.1167/17.5.23
|View full text |Cite
|
Sign up to set email alerts
|

Scan patterns during real-world scene viewing predict individual differences in cognitive capacity

Abstract: From the earliest recordings of eye movements during active scene viewing to the present day, researchers have commonly reported individual differences in eye movement scan patterns under constant stimulus and task demands. These findings suggest viewer individual differences may be important for understanding gaze control during scene viewing. However, the relationship between scan patterns and viewer individual differences during scene viewing remains poorly understood because scan patterns are difficult to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 48 publications
(79 reference statements)
3
45
0
Order By: Relevance
“…Another important extension of this work would be to conduct a scan path analysis investigating the order of saccades within a trial, to better characterise strategy use (Hayes & Henderson, 2017). Indeed, different strategies would be expected to be associated with different sequences of eye movements; for example, an equivalent fractions strategy might be characterised by more horizontal saccades at the beginning of a trial than the end.…”
Section: Discussionmentioning
confidence: 99%
“…Another important extension of this work would be to conduct a scan path analysis investigating the order of saccades within a trial, to better characterise strategy use (Hayes & Henderson, 2017). Indeed, different strategies would be expected to be associated with different sequences of eye movements; for example, an equivalent fractions strategy might be characterised by more horizontal saccades at the beginning of a trial than the end.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have used gaze measurements to understand where drivers look and to identify differences in experts' and novices' viewing behaviors in domain-specific tasks (Underwood et al, 2003;Eivazi et al, 2012). Numerous studies highlight the potential of gaze data to shed light on how humans process information, make decisions, and vary in observer behaviors (Fiedler and Glöckner, 2012;Guo et al, 2014;Hayes and Henderson, 2017;Brunyé and Gardony, 2017). Eye tracking has also long been an important tool in psycholinguistics (Cooper, 1974;Rayner, 1998;Richardson and Dale, 2005;Shao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their findings, Buswell and Yarbus suggested that gaze control in complex visual scenes is a function of the current task goals, the properties of the scene stimulus, and the properties of the viewer [ 1 , 2 ]. However, the vast majority of the scene literature has focused on the role of image properties and/or task goals [ 3 ], with little work on how viewer individual differences are related to scene gaze control [ 4 , 5 ]. As a result, very little is known about the relationship between viewer individual differences and gaze control during active scene viewing.…”
Section: Introductionmentioning
confidence: 99%
“…We [ 4 ] recently used an individual differences approach to establish an association between individual differences in viewer cognitive capacities and scan patterns during active scene viewing. Scan patterns, also referred to as scanpaths, [ 6 – 8 ], refer to the sequential pattern of stimulus fixations (See Fig 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation